Crimea and Liability of Russia and Ukraine under the European Convention on the Protection of Human Rights - Cwicinskaja, Natalia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The aim of this article is to present the liability of Russia and Ukraine regarding Crimea under the European Convention on the Protection of Human Rights. The author analyzes pending and possible prospective cases originating from the conflict around Crimea between Ukraine and Russia. Due to the inconsistency in case law of the EC-tHR it is difficult to clearly determine what state will be considered responsible for the violation of the rights of residents of Crimea resulting from the Convention. In author’s opinion the ECtHR could determine that the Russian Federation may be held respon-sible, as well as Ukraine. However, as it seems, the liability of Ukraine will be limited to the positive obligations under the ECHR.